(3GdcJGHGJ GdJGQjNjI YfO eOQSI GdeSJTQb GdESHGfj aQGfKjSch chOjQG (B/ s - (3gHI YHOGdYXje GdQGYj MSjfs; (3YHOGddg eMeO LeGd GdOjf(B: s ((3GdbGgQI (B: s (3gHI YHOGdYXje GdQGYj MSjf (B: s, 2017)
(3SYjJ ai gPG GdHMK Edi GdELGHI Yf GdYOjO ef GdJSGDdGJ GdJj JeKd eMGhQ QFjSI aj YdGbI Yde GdGSJTQGb HGdJGQjN GdESdGej(B: (3hJMOjkOG JGQjnN GdeSdejf aj GdCfOdS(B: (3hcja JfGhndrJog eOQSI Hfj chOjQG HhUagG Cgnqe eOGQS GdGSJTQGb GdESHGfj(B: (3hCf OQGSI gPg GdeOQSI GdESHGfjI JMJGL Edi eYGjjQ eZGjQI dJdc GdJj fVYgG YfO OQGSI eOGQS GdGSJTQGb GdZQHjI GdCNQi(B: (3dWHjYI GdXQha GdJGQjNjI GdJj CMGWJ HfTCI GdGSJTQGb Ch GdGSJYQGH GdESHGfj(B: (3hGdJYQa Ydi LghO eOQSI Hfj chjQG aj GdMaGX Ydi GdJQGK GdYQHj GdCfOdSj(B: (3hEMjGFg ef LOjO(B: (3heMGhdpI GdQHW Hjf GdJGQjN GdYQHj GdESdGej(B: (3hGdghjI GdESHGfjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdJGQjN h GdMVGQI GdESdGejI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGSJTQGbs; (3GdCfOdS s; (3aQGfKjSch chOjQGs